1998
DOI: 10.1073/pnas.95.3.831
|View full text |Cite
|
Sign up to set email alerts
|

Frontoparietal cortical networks for directing attention and the eye to visual locations: Identical, independent, or overlapping neural systems?

Abstract: Functional anatomical and single-unit recording studies indicate that a set of neural signals in parietal and frontal cortex mediates the covert allocation of attention to visual locations, as originally proposed by psychological studies. This frontoparietal network is the source of a location bias that interacts with extrastriate regions of the ventral visual system during object analysis to enhance visual processing. The frontoparietal network is not exclusively related to visual attention, but may coincide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
525
4
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 892 publications
(597 citation statements)
references
References 53 publications
50
525
4
13
Order By: Relevance
“…Note that these eye movement results do not invalidate our interpretation of the RT data, because attention is able to operate independently from eye movements (e.g. Corbetta, 1998). Further research is needed to elucidate the relationships between biased attention and biased eye movements in state and trait anxiety.…”
Section: Discussionmentioning
confidence: 60%
“…Note that these eye movement results do not invalidate our interpretation of the RT data, because attention is able to operate independently from eye movements (e.g. Corbetta, 1998). Further research is needed to elucidate the relationships between biased attention and biased eye movements in state and trait anxiety.…”
Section: Discussionmentioning
confidence: 60%
“…In a functional magnetic resonance imaging (fMRI) study on humans, Coull and Nobre [1998], using a combined spatial/temporal cueing task, found parts of the intraparietal sulcus (IPS) and superior parietal lobule (SPL) to be active during spatial orienting, temporal orienting, or the combination of spatiotemporal orienting. Other neuroimaging studies have found the SPL to respond mainly to the cue rather than to the target, suggesting that it is involved in setting up or maintaining an expectation, in anticipation of the target [Corbetta, 1998;Kastner et al, 1999;Shulman et al, 1999]. The same conclusion can be reached based on patient studies indicating that the posterior parietal lobe is crucial in setting up, maintaining, or disengaging spatial attention [Friedrich et al, 1998;Posner et al, 1984Posner et al, , 1987.…”
Section: Introductionmentioning
confidence: 63%
“…The searchrelated contrast (full set-single set) showed activity of the dorsolateral prefrontal cortex and the premotor cortex. Numerous previous studies reported identical or very similar areas in association with either increased effort in search [Donner et al, 2002;Nobre et al, 2003] or with related attention tasks, especially those involving endogenous attentional and oculomotor shifts [Corbetta, 1998; for reviews see Coull and Nobre, 1998;Kastner and Ungerleider, 2000]. The increased activity may reflect the additional spatial orienting associated with the presence of more items.…”
Section: Prefrontal Areasmentioning
confidence: 78%
“…Most studies of parietal cortex and attention have focused on visuospatial tasks, and, unsuprisingly, the neural systems associated with attention have been tightly coupled with the saccadic eye-movement system [16,17 ]. However, findings from the monkey physiology literature as well as recent fMRI data in humans [18,19] suggest functional specialization within the parietal lobe in mapping between different sensory modalities and different motor effectors.…”
Section: Crossmodal and Unimodal Attentional Enhancementmentioning
confidence: 99%